COMPARATIVE STUDY OF NUTRITIONAL, FUNCTIONAL AND ANTINUTRITIONAL PROPERTIES OF WHITE SORGHUM BICOLOR (SORGHUM) AND PENNISETUM GLAUCUM (PEARL MILLET) - Iyabo, OJO Olabimpe; Ibiyinka, OGUNLADE; Abimbola Deola, OLANIPEKUN (International Journal of Engineering Technologies and Management Research, 2018)
The effects of sprouting on proximate, mineral composition and functional properties of white sorghum bicolor and pennisetum glaucum were evaluated. The sorghum bicolor and pennisetum glaucum kernels obtained from Kings local market in Akure Ondo State, Nigeria and identified in the department of Agronomy Federal University of Technology, Akure were sorted and divided into two portions. The first portion was soaked for 24 hours after which it was spread on trays lined with doth and kept wet by frequent spraying of water each morning and evening for 2 days. The sprouted maize grains were oven dried at 60°C to constant weight and milled into flour. The second portion was processed into flour without sprouting, using the same method. Each of the portions was analyzed for proximate, mineral compositions and functional properties using standard methods. Sprouting of both sorghum bicolor and pennisetum glaucum grains resulted in significant increase (p<0.05) in crude protein, crude fibre, and ash content. The moisture content of sorghum bicolor increases with sprouting while that of pennisetum glaucum decreases. This decrease in the moisture content of pennisetum glaucum with sprouting implies an increase shelf life. Increase in solubility, water absorption and oil absorption capacity observed with sprouting in both sample helps in increasing the palability of the food The results showed that the sprouting process improved the nutrient composition and enhanced the functional properties of both sorghum bicolor and pennisetum glaucum with the pennisetum glaucum being found to be slightly better in terms of shelf life.